Rapid and sensitive detection of superoxide dismutase in serum of the cervical cancer by 4-aminothiophenol-functionalized bimetallic Au-Ag nanoboxs array - Xia, Ji; Chen, Gao-Yang; Li, You You; Chen, Lu; Lu, Dan (Frontiers in Bioengineering and Biotechnology, 2023)
Early, efficient and sensitive detection of serum markers in cervical cancer is very important for the treatment and prognosis to cervical cancer patients. In this paper, a SERS platform based on surface enhanced Raman scattering technology (SERS) was proposed to quantitatively detect superoxide dismutase (SOD) in serum of cervical cancer patients. Au-Ag nanoboxs (Au-AgNBs) array was made by oil-water interface self-assembly method as the trapping substrate. The single-layer Au-AgNBs array was verified by SERS for possessing excellent uniformity, selectivity and reproducibility. 4-aminothiophenol (4-ATP) was used as a Raman signal molecule, 4-ATP will be oxidized to dithiol azobenzene (DMAB) under the surface catalytic reaction with the condition of PH=9 and laser irradiation. The quantitative detection of SOD can be achieved by calculating the change of characteristic peak ratio. When the concentration is from 10 U mL-1 to 160 U mL-1, it can accurately and quantitatively detect the concentration of SOD in human serum. The whole test was completed within 20 minutes and the limit of quantitation (LOQ) is 10 U mL-1. In addition, serum samples from the cervical cancer, the cervical intraepithelial neoplasia and healthy people were tested by the platform and the results were consistent with those of ELISA. The platform has great potential as a tool for early clinical screening of cervical cancer in the future.